PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN LEMBAR KERJA SISWA BERBASIS PENEMUAN TERBIMBING PADA MATERI PELUANG KELAS XII IPA 5 SMA NEGERI 5 PONTIANAK - Rahayu Septi Ariani, S.Pd (JARDIKNAS - Jurnal Pendidikan dan Sosial, 2021)
This classroom action research is based on the low learning outcomes of students of SMA Negeri 5 Pontianak Class XII IPA 5 in mathematics, that is, most of the learning outcome indicators do not reach 75%. Researchers conducted classroom action research to improve learning outcomes by using guided discovery-based student worksheets. The use of guided discovery-based student worksheets is carried out in the distance learning process (PJJ). The design of this research refers to the process of implementing the classroom action model of Spiral Kemmis and Taggart. Time The study was conducted for 1 month from observation to two cycles. Each cycle consists of 1 meeting with a time of 60 minutes (2 x 30 lesson hours). The data analysis technique in this study was to assess the test results given to students at the end of the cycle. After being assessed, the percentage of classical learning outcomes is sought. From the results of the research carried out after the action in the first cycle, it was found that the percentage of classical student learning completeness was 58.3%. From this result, it is repeated in cycle II, with different material indicators. At the end of the action in the second cycle a test was given where the classical student mastery level was 83.3%. Based on the research analysis above, it can be concluded that learning mathematics on opportunity material in class XII IPA 5 SMA Negeri 5 Pontianak can improve learning outcomes by using guided discovery-based student worksheets. Where the increase was obtained after the second cycle was carried out.